2021
DOI: 10.3390/su13158467
|View full text |Cite
|
Sign up to set email alerts
|

Honeybee and Plant Products as Natural Antimicrobials in Enhancement of Poultry Health and Production

Abstract: The quality and safety attributes of poultry products have attracted increasing widespread attention and interest from scholarly groups and the general population. As natural and safe alternatives to synthetic and artificial chemical drugs (e.g., antibiotics), botanical products are recently being used in poultry farms more than 60% of the time for producing organic products. Medicinal plants, and honeybee products, are natural substances, and they were added to poultry diets in a small amount (between 1% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 185 publications
0
10
0
2
Order By: Relevance
“…Plant extracts, EOs, peptides, bacteriocins, and fermented substances are attractive antimicrobial alternatives to chemical antimicrobials (Aziz & Karboune, 2018). Phytochemicals have recently gained popularity as natural and safe alternatives to synthetic and artificial chemical medications (e.g., antibiotics) to improve the quality and safety characteristics of chicken products, as they are used more than 60% of the time in chicken farms for organic food production (Lika et al., 2021). Phytobiotics are antimicrobial supplements that are added to chicken feed.…”
Section: Strategies To Control Pathogen Contamination In the Chicken ...mentioning
confidence: 99%
“…Plant extracts, EOs, peptides, bacteriocins, and fermented substances are attractive antimicrobial alternatives to chemical antimicrobials (Aziz & Karboune, 2018). Phytochemicals have recently gained popularity as natural and safe alternatives to synthetic and artificial chemical medications (e.g., antibiotics) to improve the quality and safety characteristics of chicken products, as they are used more than 60% of the time in chicken farms for organic food production (Lika et al., 2021). Phytobiotics are antimicrobial supplements that are added to chicken feed.…”
Section: Strategies To Control Pathogen Contamination In the Chicken ...mentioning
confidence: 99%
“…Ces performances confirment les travaux d 'Obun et al, (2008) qui ont limité le taux du miel à 1% à la phase de finition. Il sont également en accord avec ceux du tableau de bord du poulet de chair standard (Lika et al, 2021). Par contre, le GMQ et l'IC ont été dépréciés quand le miel a été incorporé à 4%.…”
Section: Effet Du Miel Sur Le Gmq L'ic Et Le Pvunclassified
“…La mortalité étant l'un des facteurs qui freinent l'épanouissement de l'élevage avicole, l'incorporation du miel 'à 4% a engendré des taux de mortalité élevés. En se référant aux travaux effectués sous les tropiques, le taux de mortalité du lot traité en dessous de la norme universelle de 5% est acceptable en aviculture comme l'indiquent Lika et al, (2021).…”
Section: Effet Du Miel Sur La Mortalitéunclassified
“…Bees need the nectar of flowers as food to survive, while plants need pollen to spread their pollen and thus reproduce. In pollination, this task mostly falls on the bees (Aslan et al 2016;Lika et al 2021;Puvača 2018). It has been shown that the diversity of microorganisms composing the gastrointestinal system (GIS) of the honey bee is different from other living organisms.…”
Section: Introductionmentioning
confidence: 99%